How Do Teachers Perceive Limiting Factors?: Remote English Teaching Context - Suardana, Ni Luh Adelia Suarnadi; Utami, I.G.A. Lokita Purnamika; Dewi, Kadek Sintya (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2023)
The Covid-19 pandemic has forced the traditional learning system to be replaced with an online learning system or remote teaching. Several studies outside the Indonesian context state that the implementation of the remote teaching method has become a common thing to do. However, in the Indonesian context, the remote teaching method is something new, so that it makes teachers face several problems during the learning process. Thus, the factors that limit the implementation of remote teaching are also definitely different, especially in the Indonesian context. This study aims to find out more clearly about teacher perceptions through limiting factors in the implementation of remote teaching related to what is found in the literature review matrix from several studies outside of the Indonesian context and in the Indonesian context. Many researchers have examined this case, but most only use one research method, qualitative or quantitative. Therefore, this study tries to present different data using mixed methods (qualitative methods using a literature review matrix and interviews, then quantitative methods using questionnaires) so that the data obtained is stronger and more valid. The participants in this study were three high school English teachers. The results of this study indicate that there are nine limiting factors found in the literature review matrix and these factors were confirmed by the subjects. Therefore, the obstacles in remote teaching must be identified to be used for improving the learning process itself, for the government (Ministry of Education and Culture), for the school, teachers, and students.